All Days 2014
DOI: 10.2118/170804-ms
|View full text |Cite
|
Sign up to set email alerts
|

Extending the Life of Mature Assets: How Integrating Subsurface & Surface Knowledge and Best Practices Can Increase Production and Maintain Integrity

Abstract: Many producing assets in the world have reached the so-called mature phase of development. Some of these assets have been producing for 30 to 40 years or more, which is typically beyond the design life, and have reached a water to oil ratio of 3 to 9 or more. There are many issues that affect the productivity and economic viability of these fields. Some of the challenges include integrity uncertainty in the wells, flow lines, and facilities; production bottlenecks due to the shift in gas, oil and water ratios;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The authors found that the TDS concentration of produced water in the western United States is between 1000 mg/L and 400,000 mg/L, but the average TDS concentration of produced water from most formations was less than 100,000 mg/L. Additionally, in the same study [10] covering produced water in the western United States, the produced water, oil and grease content was found to be in the range of 40 mg/L to 2,000 mg/L. The properties and composition of contaminants in produced water vary considerably in different geological formations; therefore, in this study, produced water samples from various oilfields in Kuwait were analyzed to determine their physical properties and dissolved substances, which are useful in determining the environmental and economic risks from discharging such water.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…The authors found that the TDS concentration of produced water in the western United States is between 1000 mg/L and 400,000 mg/L, but the average TDS concentration of produced water from most formations was less than 100,000 mg/L. Additionally, in the same study [10] covering produced water in the western United States, the produced water, oil and grease content was found to be in the range of 40 mg/L to 2,000 mg/L. The properties and composition of contaminants in produced water vary considerably in different geological formations; therefore, in this study, produced water samples from various oilfields in Kuwait were analyzed to determine their physical properties and dissolved substances, which are useful in determining the environmental and economic risks from discharging such water.…”
Section: Introductionmentioning
confidence: 75%
“…The salt content in produced water is an important matter of concern in the oil production sector because the salinity and Total Dissolved Solids (TDS) of the produced water can be higher than the salinity and TDS of seawater, as shown in a previous study [10]. The authors found that the TDS concentration of produced water in the western United States is between 1000 mg/L and 400,000 mg/L, but the average TDS concentration of produced water from most formations was less than 100,000 mg/L.…”
Section: Introductionmentioning
confidence: 78%
“…Flow assurance encompasses a broad spectrum of disciplines within subsea production engineering [13]. It is primarily concerned with guaranteeing uninterrupted and efficient flow of hydrocarbons from the reservoir to the processing facility [2]. Several key aspects contribute to this overarching objective, including: hydrate management, wax management, scale management, slugging & flow regimes and erosion & corrosion.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, mercury speciation analysis in PW samples requires efficient separation of the analytes before derivatization [48]. as the samples present very high chloride content (salt supersaturation is common).…”
Section: Produced Watersmentioning
confidence: 99%
“…Since the method aimed at the determination of Hg 2+ and CH3Hg in PW, the effects of oil and salt content on the generation of Hg vapor was studied. Sodium chloride is the main inorganic component in PW, being present at higher concentrations than in seawater (typically from 30 to 400 g L -1 ) [48,142]. Because of the high formation constants, at high concentrations of chloride, it is possible that Hg 2+ tend to form stable HgCln (2-n) complex ions that may hinder the reduction of Hg 2+ to Hg 0 [143][144][145].…”
Section: Effect Of Oil and Salt Content In The Generation Of Hg Vapormentioning
confidence: 99%